Denticulobasis and Tuberculobasis, new genera close to Leptobasis, with description of ten new species (Odonata: Coenagrionidae) - Machado, Angelo B. M. (Zootaxa, 2009)
Two new genera, Denticulobasis and Tuberculobasis, are described. Denticulobasis contains three species: D. dunklei sp. nov. from Loreto, Peru, and D. garrisoni sp.nov. and D. ariken sp. nov. from Rondônia, Brazil. Tuberculobasis includes 12 spp., all from South America, seven of which are new, viz.: T. arara sp. nov. from Rondônia, Brazil, T. geijskesi sp.nov. from Suriname, T. guarani sp. nov. from São Paulo, Brazil, T. karitiana sp.nov. from Rondônia, Brazil, T. macuxi sp.nov. from Roraima, Brazil, T. tirio sp. nov. from Pará, Brazil, and T. williamsoni sp.nov. from Colombia and Venezuela. Five species are herein transferred from Leptobasis Selys, 1877 to Tuberculobasis: L. cardinalis (Fraser, 1946), L. costalimai Santos, 1957, L. inversa Selys, 1876, L. mammilaris Calvert, 1909, and L. yanomami De Marmels, 1992. The new genera are close to Leptobasis; differences between them are analyzed and their diagnostic characters are described. In addition, diagnostic characters of females of three species of Tuberculobasis, most likely new, are illustrated but they are not named. A key for males and females of Tuberculobasis is provided, and an attempt to understand their life cycle is made.